Nutritional and Functional Properties of Quinoa (Chenopodium quinoa Willd.) Chimborazo Ecotype: Insights into Chemical Composition - Paola Arguello-Hernández; Iván Samaniego; Alex Leguizamo; María Josefa Bernalte-García; María Concepción Ayuso-Yuste (Agriculture, 2024)
Quinoa is known for its high nutritional value and adaptability; however, there is a lack of data about the chemical composition of quinoa produced in Ecuador, especially the Chimborazo ecotype. Our research aims to evaluate the nutritional components of Chimborazo quinoa. This knowledge (chemical composition) can help to improve cultivation and farmers’ understanding. Samples were collected from 49 plots at four altitude ranges (3000–3200; 3201–3300; 3301–3400; 3401–3533) m.a.s.l. Each sample of 2 kg quinoa was cleaned, dried (32 °C/15 h), and stored at −20 °C before analyzing water activity, proximate composition, mineral content, antioxidant activity, and functional compounds. The data were analyzed using ANOVA and mean comparison, Pearson correlation, and principal component analysis. The Chimborazo ecotype shows protein content comparable to or exceeding other global quinoa cultivars. Statistical analysis revealed that altitude had a minimal influence on quinoa’s chemical composition, resulting in overlapping altitude-based clusters. Complex relationships between quinoa variables were identified, which varied with altitude. These findings suggest that cultivation of high-quality quinoa across a range of altitudes is feasible without compromising its intrinsic quality. Moreover, the extensive and diverse results from our study provide a solid foundation for further plant breeding and the development of specialized quinoa varieties.